Clinical research Comparative investigation of antioxidant activity of human serum blood by amperometric, voltammetric and hemiluminescent methods; Archives of Medical Science; Vol. 12, iss. 1 - Plotnikov E. V. Evgeny Vladimirovich; Korotkova E. I. Elena Ivanovna; Voronova O. A. Olesya Aleksandrovna; Sazhina N. N. Nataljya Nikolaevna; Petrova E. V. Ekaterina Viktorovna; Artamonov A. I. Anton; Chernyavskaya L. I. Lyudmila Ivanovna; Dorozhko E. V. Elena Vladimirovna (2016, 2016)
Title screen